2015
DOI: 10.1016/j.jconrel.2015.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Disarmed anthrax toxin delivers antisense oligonucleotides and siRNA with high efficiency and low toxicity

Abstract: Inefficient cytosolic delivery and vector toxicity contribute to the limited use of antisense oligonucleotides (ASOs) and siRNA as therapeutics. As anthrax toxin (Atx) accesses the cytosol, the purpose of this study was to evaluate the potential of disarmed Atx to deliver either ASOs or siRNA. We hypothesized that this delivery strategy would facilitate improved transfection efficiency while eliminating the toxicity seen for many vectors due to membrane destabilization. Atx complex formation with ASOs or siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The method seems to be efficient and of low toxicity. Coupling this delivery system with the targeting properties of engineered PA could be of great use in in vivo downregulation of target genes [ 104 ]. Another study showed that PA was also capable of translocating non-canonical polypeptides, nicely illustrating the broad translocation ability of the PA pore [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method seems to be efficient and of low toxicity. Coupling this delivery system with the targeting properties of engineered PA could be of great use in in vivo downregulation of target genes [ 104 ]. Another study showed that PA was also capable of translocating non-canonical polypeptides, nicely illustrating the broad translocation ability of the PA pore [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vero cells (ATCC number CCL-81), were cultured as previously described (Dyer et al, 2015). Purified GST-GFP in PBS was filter sterilised using a 0.2 micron filter (Milipore Ltd, Hertfordshire, UK) and added to cultured cells at a concentration of 1 mg/mL in the presence of 200 µM Leupeptin (Sigma-Aldrich Company Ltd., Dorset, UK).…”
Section: Methodsmentioning
confidence: 99%
“…This "pulse" of GST-GFP was added to complete cell culture media and incubated for 4 hours at 37 o C. The cells were then washed three times with fresh sterile PBS and returned to incubate in complete media for an additional 20h at 37 o C in 5% (v/v) CO2. The cells were then washed 3 times in PBS and fixed with either cold methanol or formaldehyde (as noted) and as previously described (Dyer et al, 2013;Dyer et al, 2015). Immunostaining was performed as previously described (Richardson et al, 2004;Richardson et al, 2008;Dyer et al, 2013;Dyer et al, 2015) using EEA1 (BD Bioscience,) LAMP1 or LAMP2 specific monoclonal antibodies (DHSB hybridoma bank, University of Iowa, USA) as previously described (Richardson et al, 2004;Richardson et al, 2008;Dyer et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The activated PA can oligomerise into heptamers, or the less abundant octamers either in solution or at the cell surface after receptor binding [52]. The exact and specific order of events is controversial as one report details a lack of furinlike proteases at the cell surface and another shows that PA63 can oligomerise into annular structures in 50% serum in the absence of receptors [53]. Further, oligomerisation has been documented in serum after the administration of PA83 in vivo [54].…”
Section: Strategies To Evade Endolysosome Destructionmentioning
confidence: 99%
“…It is of note that after translocation into the ILV lumen, the LF and EF are effectively protected from lysosomal hydrolases. Given that the multimeric PA pore is described as a cation selective channel [58] that requires cargo to unfold in order to undergo translocation [62], the observation that supramolecular assemblies containing large anionic components can traverse the PA pore to access the cytosol is of direct interest here [53]. Recently published data describe the cytosolic translocation of both siRNA, antisense oligonucleotides [53], plasmid DNA [62] and plasmid DNA polylysine complexes [63], though it should be noted that plasmid polylysine complexes have been known to rupture endosomal membranes without anthrax toxin components [64].…”
Section: Strategies To Evade Endolysosome Destructionmentioning
confidence: 99%